The Wage Gap between Francophones and Anglophones: A Canadian Perspective, 1970-2000 - Albouy, David (The Canadian Journal of Economics / Revue canadienne d'Economique, 2008)
The wage gap between Francophone and Anglophone men from 1970 and 2000 fell by 25 percentage points within Quebec, but only by 10 points Canada-wide, largely because the wages of Quebec Anglophones fell by 15 points relative to other Canadian Anglophones. Accordingly, the Canadian measure of the Francophone gap better reflects the changing welfare of Francophones than the Quebec measure. Over half of the reduction in the Canadian Francophone wage gap is explained by rising Francophone education levels. In Quebec, the declining number and relative wages of Anglophone workers is best explained by a falling demand for English-speaking labour. /// L'écart de salaires entre les hommes francophones et anglophones est tombé de 25 points de pourcentage au Québec entre 1970 et 2000, mais seulement de 10 points à l'échelle canadienne, largement parce que les salaires des anglophones au Québec sont tombés de 15 points par rapport aux autres canadiens anglophones. En conséquence, la mesure canadienne de l'écart prend mieux la mesure du changement de bien-être des francophones que la mesure québécoise. Plus de la moitié de la réduction dans l'écart au niveau canadien s'explique par l'accroissement des niveaux d'éducation des francophones. Au Québec, le nombre en déclin des travailleurs anglophones et la chute de leurs salaires relatifs s'expliquent par un déclin dans la demande de travailleurs parlant anglais.